Cinética da fermentação ruminal de dietas contendo leguminosas taniníferas - Rodrigues, Maria Juciara Silva Teles (2017)
A total of five diets, were evaluated. The diets composed was by elephant grass hay with inclusion of concentrate (corn and soybean meal) or four tropical leguminous: pigeonpea, gliricidea, jureminha and leucaena. The diets used were: Control kept at elephant grass hay concentrate (25% for corn and soybean meal) ratio of 50:50, Gliricídia: kept at a elephant grass hay gliricídia hay ratio of 50:50, Leucena: kept at a elephant grass hay leucena hay ratio of 50:50, Guandu: kept a elephant grass hay guandú hay ratio of 50:50 and Jureminha kept at a elephant grass hay: jureminha hay ratio of 50:50. Digestibility for: dry matter (DDM), organic matter (DOM) and neutral detergent soluble fibre (DNDSF) estimated was. Degradation of dry matter (DegDM) and organic matter (DesOM), in vitro gas production (IVGP), ruminal fermentation parameters: pH, NH3N (ammonia nitrogen) and partitioning factor (PF) after in vitro incubation of 48 hours. The control diet showed higher values for digestibility and degradability parameters, as well as higher final gas production volume (FGV), higher gas production rate (S) and shorter colonization time (L), resulting in higher cumulative production gas during 48 hours of incubation (P<0.05). The Guandu diet showed the lowest, however satisfactory results for DDM, DOM, DNDSF, DegDM and DegOM, and lower cumulative total gas production (P<0.05), the Gliricidia diet showed higher values for DDM, DOM, FGV,GR and L in comparison to Guandu diet (P<0.05). The diets Gliricidia, Leucena, Guandu and Jureminha, provide alternative strategies for feeding ruminants. However, the Gliricidia diet showed a greater efficiency to substitute concentrate food, due to show similar results that observed for control diet.